Television talk shows and the public sphere - Juliana Abdul Wahab (Universiti Kebangsaan Malaysian, 2011)
The concept of public sphere, which was first introduced by Habermas, refers to the notion of a public domain or arena where discourses on various issues take place in society. Central to Habermas’ idea of public sphere is the principle of equal opportunity for everyone to participate in a debate, and the ability of individuals to communicate, negotiate and articulate ideas amongst themselves. Television talk show in this respect could be seen as a mechanism to promote the idea of public sphere. In Malaysia, television talk show is fast becoming a popular television genre and has an important place in television scheduling. In this regard, the latest development in local television scenario necessitates an in-depth investigation into the extent to which the concept of public sphere vis-a-vis talk show can be regarded as domain where various issues about Malaysia are discussed.